Twin-width and Polynomial Kernels - Bonnet, Édouard; Kim, Eun Jung; Reinald, Amadeus; Thomassé, Stéphan; Watrigant, Rémi (Algorithmica, 2022)
We study the existence of polynomial kernels, for parameterized problems without a polynomial kernel on general graphs, when restricted to graphs of bounded twin-width. Our main result is that a polynomial kernel for k -Dominating Set on graphs of twin-width at most 4 would contradict a standard complexity-theoretic assumption. The reduction is quite involved, especially to get the twin-width upper bound down to 4, and can be tweaked to work for Connected k -Dominating Set and Total k -Dominating Set (albeit with a worse upper bound on the twin-width). The k -Independent Set problem admits the same lower bound by a much simpler argument, previously observed [ICALP ’21], which extends to k -Independent Dominating Set , k -Path , k -Induced Path , k -Induced Matching , etc. On the positive side, we obtain a simple quadratic vertex kernel for Connected k -Vertex Cover and Capacitated k -Vertex Cover on graphs of bounded twin-width. Interestingly the kernel applies to graphs of Vapnik–Chervonenkis density 1, and does not require a witness sequence. We also present a more intricate O ( k 1.5 ) vertex kernel for Connected k -Vertex Cover . Finally we show that deciding if a graph has twin-width at most 1 can be done in polynomial time, and observe that most optimization/decision graph problems can be solved in polynomial time on graphs of twin-width at most 1.